Two years after pulmonary vein isolation guided by ablation index—a multicenter study. Issue 3 (15th March 2022) - Sousa, Pedro A.; Puga, Luís; Adão, Luís; Primo, João; Khoueiry, Ziad; Lebreiro, Ana; Fonseca, Paulo; Lagrange, Philippe; Elvas, Luís; Gonçalves, Lino
Abstract: Background: The use of the Ablation Index (AI) software for paroxysmal atrial fibrillation (AF) has been associated with higher acute effectiveness and higher 1‐year arrhythmia freedom. There is, however, a lack of data concerning longer follow‐up. We aim to evaluate the 2‐year outcomes after a standardized AI‐guided pulmonary vein isolation (PVI). Methods: Prospective, multicenter study of consecutive patients referred for paroxysmal AF ablation from January 2018 to July 2019. PVI was guided by a tailored AI value (≥500 for anterior segment, ≥450 for the roof segments and inferior segments, and 400 for the posterior wall) and an ILD ≤6 mm. The primary endpoints were acute and long‐term effectiveness. Results: The study included 218 (842 PV) patients (61% males, median age of 60 [IQR 49–68] years) with paroxysmal AF. First‐pass isolation was obtained in 93% of the patients, with an acute reconnection occurring in 10.6% of the patients (3.2% of the PV) following adenosine trial. After a median follow‐up of 26 (IQR 20–30) months, freedom from any documented atrial arrhythmia was 83.4%, off‐AAD. The rate of adverse events was 1.4%. Although procedural parameters differ across centers ( p  < 0.001), the acute ( p  = 0.56) and long‐term effectiveness ( p  = 0.83) were consistent between centers. Conclusions: Patients with paroxysmal AF submitted to an AI‐guided PVI workflow presented high arrhythmia freedom at 2‐years of follow‐up. Abstract : This study presents the longest follow‐up after pulmonary vein isolation guided by the Ablation Index software; A tailored, standardized AI‐guided demonstrates a low acute pulmonary vein reconnection and an 83% freedom from sustained atrial arrhythmia at 2‐years of follow‐up;The acute and long‐term effectiveness obtained in this study appears to be reproducible across the different centers.